MODEL INTERVENSI SUPPORTIVE EDUCATIVE SYSTEM BERBASIS INTEGRASI SELF CARE TERHADAP PENGETAHUAN DAN PRAKTIK PEMBERIAN MAKAN PADA IBU BALITA GIZI KURANG : MODEL INTERVENSI SUPPORTIVE EDUCATIVE SYSTEM BERBASIS INTEGRASI SELF CARE TERHADAP PENGETAHUAN DAN PRAKTIK PEMBERIAN MAKAN PADA IBU BALITA GIZI KURANG - Ayupir, Ariyanto; Nelista , Yosefina; Fembi, Pembronia Nona Fembi (Bina Generasi : Jurnal Kesehatan, 2024)
The nutritional status of children under five is a reflection of the nutritional status of the community, nutritional problems arise if the intake of nutrients consumed with nutritional needs is not appropriate. Malnutrition status in toddlers has a negative impact on growth disorders and causes low cognitive abilities and Intelligence Quotient values. Supportive educative system is a method of education or providing education using various methods such as teaching, guiding, and providing environment. The purpose of this study was to analyze the knowledge and practice of feeding underweight mothers before and after being given a supportive educative system intervention based on self care integration. The type of research used is a quasi-experimental research design with one group pretest posttest design. The population in this study were all underweight children under five years of age in the working area of ​​the Magepanda Health Center as many as 36 people, the sampling technique in this study was using a non-probability sampling technique by means of saturated sampling. The instrument for measuring feeding practices was measured using a modified questionnaire from the Child Feeding Questionnaire. Data collection includes pretest, intervention and posttest. Wilcoxon test results show that before and after being given the intervention Supportive Educative System Based on Integration of Self Care and Family Centered Nursing gives a price (p-value 0.000 less than = 0.05), then Ho is rejected. Ha is accepted. This shows that there is a significant effect caused by the intervention of the Supportive Educative System Based on Integration of Self Care and Family Centered Nursing.